Evaluation of coagulation profile in dogs with ACTH-dependent hyperadrenocorticism compared to healthy dogs by rotational thromboelastometry (ROTEM) - Romão, F. G. [UNESP]; dos Santos, B.; Mora, S. E.V. [UNESP]; Gonçalves, D. S. [UNESP]; de Marco, V.; Lopes, P. A.; Tsunemi, M. H. [UNESP]; Takahira, R. K. [UNESP] (Elsevier, 2024)
Despite their low morbidity, thromboembolic events in hyperadrenocorticism are associated with high mortality. Identifying the main hemostatic abnormalities will improve the prophylactic approach of these canine patients. The aim of this study was to evaluate hemostatic alterations related with ACTH-dependent HAC and its association with hypercoagulable state. For this purpose, 25 dogs diagnosed with ACTH-dependent HAC were compared with 28 healthy dogs as a control group. The hemostatic variables included platelet count, antithrombin, fibrinogen, D-dimer, PT, aPTT, rotational thromboelastometry (ROTEM) and platelet aggregation. Results showed a hypercoagulable state in 32% (8/25) dogs by ROTEM, which had at least 2 of the next features: decreased coagulation time (CT) or clot formation time (CFT) on INTEM (5/25) or EXTEM (4/25); increased maximum clot firmness (MCF) on INTEM (9/25), EXTEM (6/25) and FIBTEM (9/25). These same variables had a significant difference (P≤ 0.05) compared with the control group, as well as the parameters of α-angle and CT. Median fibrinogen levels (310 vs.178 mg/dL), mean platelet aggregation (11.1 vs. 7.9 Ohms), median platelet count (360 vs. 225 ×103/µL) and mean antithrombin activity (140 vs. 119%) were increased in ACTH-dependent HAC dogs compared to control group. PT (7.1 vs. 8.0 seconds) and aPTT (11.6 vs. 15.2 seconds) were also shortened in ACTH-dependent HAC dogs. Our findings confirm the presence of a hypercoagulable tendency in dogs with HAC. Although multifactorial, fibrinogen concentration and MCF FIBTEM showed the relevance of this protein for hypercoagulability in HAC.
Keywords: Antithrombin; Fibrinogen; Hypercoagulability; Thrombocytosis; Thromboelastometry